Implementation of Blended Learning For Early Children in Kindergarten Bina Kebajikan - Luli Andriany (Eduvest - Journal of Universal Studies, 2021)
The covid 19 pandemic that has hit the whole world has caused changes in various aspects of life, one of which is the world of education from the PAUD/TK, SD, SLTP, SLTA to tertiary levels must take online learning to break the chain of the spread of the covid 19 virus. This research uses the method qualitative (Classroom Action Research) which refers to observations and interviews. The learning carried out for early childhood uses the Blended-Learning method which is an approach using a mixed method between face-to-face and the use of technology for distance learning. Learning using blended-learning is suitable for the development of early childhood learning because teachers can directly interact or face-to-face through online media such as videocall, zoom, and google meet. Where this learning can also increase children's enthusiasm, school from home with parental assistance. The goal is that learning can run effectively and children can understand what the teacher is saying. The results showed that children can interact well, and are enthusiastic about doing activities that will be carried out the same as in schools in general, teachers can see the active role of students in activities, the active role of parents accompanying children at home during activities, teachers can assess directly how the role of the child during the activity, whether it is capable enough or still being helped. So that an assessment is achieved according to aspects of early childhood development.